Cord Blood Alkaline Phosphatase as A Predictive Biomarker for Neonatal Jaundice in Term and Near-Term Neonate - Nagar , Devyash; Shah, Prashant (International Journal of Medical Research, 2025)
Background: Neonatal hyperbilirubinemia (NNHB) is a common condition that can lead to severe neurological complications if untreated, particularly in resource-limited settings where early detection is challenging. This study evaluates cord blood alkaline phosphatase (ALP) as a non-invasive biomarker for predicting neonatal jaundice. Methods: A prospective observational study was conducted with 95 healthy term and near-term neonates (>35 weeks gestation) at Krishna Hospital, Karad, India, from May 2023 to November 2024. Cord blood ALP levels were analyzed at birth, with clinical follow-up for jaundice over 7 days. Neonates with conditions affecting liver or hematopoiesis or hematopoiesis were excluded. Data on demographic, clinical, and laboratory parameters, including hemoglobin and bilirubin levels, were collected. Statistical analysis was performed using chi-square tests and t-tests to assess associations with jaundice. Results: Of 95 neonates, 44 (46.3%) developed jaundice. Jaundiced neonates had significantly higher cord blood ALP (345 ± 85 IU/L vs. 141 ± 37 IU/L, P <0.001) and lower hemoglobin (14.5 ± 3.2 g/dL vs. 16.5 ± 3.0 g/dL, P < 0.001) compared to non-jaundiced neonates. Parental consanguinity was more prevalent in jaundiced neonates (25% vs. 9.8%, P = 0.048). No significant associations were found with gestational age, birth weight, or breastfeeding. Conclusion: Elevated cord blood ALP is a promising biomarker for early identification of neonates at risk of jaundice, particularly in resource-constrained settings. Future multicenter studies are needed to validate ALP thresholds and explore genetic factors linked to consanguinity for improved NNHB management.